Происхождение литовских интонаций - Скляренко, Віталій Григорович (Baltistica, 1990)
THE ORIGIN OF INTONATION IN LITHUANIAN The article deals with the origin of intonation both in the Aukštaičiai and Žemaičiai dialects. In proto-Lithuanian dialects and common Lithuanian language there was a rise-fall intonation that could have been monosyllabic (if the intonated syllable was long) and disyllabic (if the first intonated syllable was short). In proto-Lithuanian dialects the syllable obtaining a short diphthongal combination (a short vowel + sonant) was short. The tonic and dynamic peaks in the rise-fall intonation were at the end of the rising part of tone (either at the end of the first mora of the long vowel or at the end of short vowel of the first intonated syllable). In Aukštaičiai dialects, which constituted the basis of the Lithuanian literary language, the old intonational differences had been entirely lost, and the new ones were formed as a combination of length with iktus (the dynamic peak of the old intonations). The combination of length with iktus in the first mora gave origin to falling intonation (acute), and the combination of length with iktus in the second mora produced rising intonation (circumflex). The common Lithuanian monosyllabic rise-fall intonation was transformed into Lithuanian falling intonation. The common Lithuanian disyllabic rise-fall intonation, in cases when the first intonated syllable became lengthened (in connection with this the rise of the tone in proto-Aukštaičiai dialects covered the whole lengthened syllable, and the tonic and dynamic peaks occurred at the end of the rising part of the tone) was transformed into the Lithuanian rising intonation in the lengthened syllable. The old intonational differences in Žemaičiai dialects were not entirely lost but were essentially changed. The common Lithuanian monosyllabic rise-fall intonation was transformed into the Žemaičiai broken intonation. The common Lithuanian disyllabic rise-fall intonation in cases when the first intonated syllable became lengthened (in connection with this the fall of the tone in proto-Žemaičiai dialects shifted from the second intonated syllable to the first intonated syllable which became lengthened) was transformed into the Žemaičiai rising intonation in the lengthened syllable.